Pyrolysis of azolla, sargassum tenerrimum and water hyacinth for production of bio-oil. (October 2017) - Biswas, Bijoy; Singh, Rawel; Krishna, Bhavya B; Kumar, Jitendra; Bhaskar, Thallada
Abstract: Pyrolysis of azolla, sargassum tenerrimum and water hyacinth were carried out in a fixed-bed reactor at different temperatures in the range of 300–450 °C in the presence of nitrogen (inert atmosphere). The objective of this study is to understand the effect of compositional changes of various aquatic biomass samples on product distribution and nature of products during slow pyrolysis. The maximum liquid product yield of azolla, sargassum tenerrimum and water hyacinth (38.5, 43.4 and 24.6 wt.% respectively) obtained at 400, 450 and 400 °C. Detailed analysis of the bio-oil and bio-char was investigated using 1 H NMR, FT-IR, and XRD. The characterization of bio-oil showed a high percentage of aliphatic functional groups and presence of phenolic, ketones and nitrogen-containing group. The characterization results showed that the bio-oil obtained from azolla, sargassum tenerrimum and water hyacinth can be potentially valuable as a fuel and chemicals.